I want to show the following equality (using logical connectives, not venn diagrams)
Show that: $$(A ∩ B) ▵ C = (A ▵ C) ▵ (A \setminus B)$$
$A ▵ B$ is defined as: $(A ∪ B) \setminus (A ∩ B)$
My attempt:
If I expand the symmetric difference symbol $▵$ in the original equality I get:
$$((A ∩ B) ∪ C) \setminus ((A ∩ B) ∩ C) =$$
$$(((A ∪ C) \setminus (A ∩ C)) ∪ (A \setminus B)) \setminus (((A ∪ C) \setminus (A ∩ C)) ∩ (A \setminus B))$$
So now I want to write the second statement in the equality with logical connectives and reduce it to the first one:
$$((A \land B) \lor C) \land \lnot ((A \land B) \land C) =$$
$$(((A \lor C) \land \lnot (A \land C)) \lor (A \land \lnot B)) \land \lnot (((A \lor C) \land \lnot (A \land C)) \land (A \land \lnot B)) =$$
But I am stuck here. I don't really know where to begin...